2020
DOI: 10.1039/c9nr10366j
|View full text |Cite
|
Sign up to set email alerts
|

Thermal robustness of magnetic tunnel junctions with perpendicular shape anisotropy

Abstract: Perpendicular Shape Anisotropy based storage layer offers a bulk anisotropy much more robust against thermal fluctuations than the interfacial anisotropy, allowing to reduce the temperature dependence of the coercivity of sub-20 nm MTJ cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 30 publications
1
24
0
Order By: Relevance
“…Compared to previous reports of multi‐level switching with junction shape in nanowires, [ 18–20 ] the circular junctions used in our study are much preferred in p‐STT‐MRAMs. [ 2,21 ] Recent studies also showed the multi‐level states in 6 µm diameter in‐plane MTJs through the magnetic field sweeping. [ 22 ] However, the current‐induced switching is more advantageous in today's memories allowing a shared path for writing‐reading operation, but requiring the perpendicular anisotropy to reduce the writing current.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to previous reports of multi‐level switching with junction shape in nanowires, [ 18–20 ] the circular junctions used in our study are much preferred in p‐STT‐MRAMs. [ 2,21 ] Recent studies also showed the multi‐level states in 6 µm diameter in‐plane MTJs through the magnetic field sweeping. [ 22 ] However, the current‐induced switching is more advantageous in today's memories allowing a shared path for writing‐reading operation, but requiring the perpendicular anisotropy to reduce the writing current.…”
Section: Resultsmentioning
confidence: 99%
“…[ 16,18 ] In MTJs, the current driven DW motion was reported in the U shape [ 19 ] and T shape [ 20 ] nanowires with a very large aspect ratio, which cannot be directly implemented into memories since an aspect ratio close to 1 is expected. [ 21 ] The multi‐domain state was lately revealed in in‐plane MTJs through magnetic field sweeping, [ 22 ] but the demonstration of current‐driven multi‐state with perpendicular anisotropy is required for memory application. The magnetic domain properties of perpendicular CoFeB have been studied in unpatterned thin films.…”
Section: Introductionmentioning
confidence: 99%
“…Perpendicular Shape Anisotropy (PSA) has been recently implemented in the storage layer of STT-MRAM to enhance its downsize scalabilty [49][50][51][52]. In these previous studies, the storage layer thickness was increased in order to enhance the thermal stability down to sub-10nm diameters where conventional STT-MRAM based on interfacial anisotropy is no longer stable.…”
Section: Substitution Of Co/pt By Using Psamentioning
confidence: 99%
“…The energy barrier, ∆ E, which divides the two stable opposite states (AP, P), depends in a complex way on both M s and K u (and on the free layer volume) [19]. Nonetheless, in macrospin regime (r<30 nm) the barrier height, could be approximated, in a simplified way, as:…”
Section: B Thermal Stability and Retention Time Of The Stored Informationmentioning
confidence: 99%